Development of Arctic Natural Resources by the Industrialized Countries in the Context of Energy, Ecological and Economic Security - DUDIN, Mihail Nikolaevich; LYASNIKOV, Nikolaj Vasilevich; SEKERIN, Vladimir Dmitriyevich SEKERIN; GOROHOVA, Anna Evgenevna; BANK, Sergey Valeryevich; BURLAKOV, Vyacheslav Viktorovich (Journal of Environmental Management and Tourism, 2016)
This article is devoted to the study and generalization of the most problematic aspects associated with the development of the Arctic zone. The purpose of this article is to analyze the ratio of social and economic benefits and potential environmental hazards that could lead to catastrophic consequences for the whole of modern civilization. To achieve this goal, the problems have been solved associated with historic overview of the periods of global expansion and development of the Arctic, research of the development of technologies that are used or will be used for development of the Arctic, research and analysis of potential environmental risks that may arise as a result of the aggressive expansion of the Arctic coastal and other states.
Keywords: Arctic; natural resources; economic security; environmental risks; ecological changes